Cultural odyssey in the metaverse: investigating the impact of virtual technologies on tourist reuse behavior and social sustainability - Chunyu Jiang; Seuk Wai Phoong; Sedigheh Moghavvemi (Humanities & Social Sciences Communications)
Abstract This study investigates the impact of advanced digital technologies, particularly virtual reality (VR), on the sustainability of cultural heritage tourism, focusing on user reuse behavior. Amid the challenges posed by the COVID-19 pandemic, traditional tourism has gravitated toward immersive technologies to enhance economic, social, and environmental sustainability. Utilizing the Stimulus-Organism-Response (S-O-R) model, this research examines how existential authenticity and immersion influence cultural attachment, satisfaction, and subsequently, intent to reuse and social sustainability. The methodology employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze user data. The results indicated that while existential authenticity significantly affects cultural attachment and satisfaction, immersion does not directly impact satisfaction, contradicting previous research. Cultural attachment emerges as a pivotal variable, influencing satisfaction, intention to reuse, and social sustainability, underscoring its critical role in enhancing user experiences in virtual exhibitions. The study recommends that VR experiences be designed to evoke existential authenticity to improve cultural attachment and user satisfaction, which are essential for advancing social sustainability. This research contributes empirical evidence to the role of immersive technologies in fostering social sustainability within cultural heritage tourism and offers practical insights for stakeholders in the sector.